Estimating consumer surplus of Kilim Karst Geoforest Park using travel cost method - Zameli, Nurul Hikmah; Mohammad Afandi, Syamsul Herman; Samdin, Zaiton; Shuib, Ahmad (Faculty of Forestry, Universiti Putra Malaysia, 2013)
This study examines the estimation of consumer surplus (CS) using basic travel cost method to attain the value of recreational experiences of tourists in Kilim Karst Geoforest Park (KKGP). A demand function is derived using linear regression analysis using SPSS. A descriptive analysis is conducted to describe visitors‟ socio-demographic. This study employed the visit rate per year of respondents as the dependent variable while travel cost of tourists as the independent variable. The findings show travel cost is significant at 5% level. There is a negative relationship between frequency of visit and the travel cost and this supports the demand theory. The CS is estimated at RM 32, 427.43 per year at zero cost. The estimated average CS for KKGP is RM 547/person/visit/year. This value is relatively high compared to other studies, probably due to omission on other demand determinants. The study gives basic understanding on how people obtain satisfaction upon their visit to KKGP, which may benefit the management on the knowledge of such information in their area.